Advanced technologies in controlling training process for qualified athletes - Kutek, T.; Akhmetov, R.; Vovchenko, I.; Korneychuk, N.; Shaversky, V.; Yavorska, T.; Bereziuk, Y.; Garlinska, A.; Kruk, A.; Tolkach, V.; Gedziuk, D.; Nabokov, Y.; et al. (International Journal of Applied Exercise Physiology, 2020)
The effectiveness of a push-off in many sports is an integral indicator of skill, since when performing a push-off, literally all organs and systems of the body get engaged in interaction. The push-off (take-off in high jump) sets the dynamic foundation of high sports results and creates conditions for effective interaction of internal and external forces. Using special tests, it is possible to determine the functioning level of discrete body systems, which directly define a result in a sports exercise, thus making it possible in the process of training sessions to purposefully influence the stimulation of individual systems, increasing their functioning level. This situation requires specialists to develop priority areas that would allow them to discover the reserves for achieving high sports results. Particularly acute is the problem associated with the use of modern technological approaches that allow monitoring the condition of athletes and their readiness for competitions.